Dimensi Ekonomi Politik dalam Konflik Perebutan Sumber Kekuasaan Arab Islam - Khoirul Anwar; Nazar Nurdin; Muslich Shabir (Lembaga Kajian dan Pengembangan Sumberdaya Manusia, 2020)
Abstrak Tulisan ini menganalisis upaya Nabi Muhammad Saw. dalam mewujudkan peradaban Islam dengan merebut sumber ekonomi dan komunitas dari penguasa Arab pra-Islam. Upaya Nabi Muhammad Saw. yang berhasil melangkahi aristokrat Mekkah (Bani Umayyah) menunjukkan bahwa Nabi Muhammad SAW tidak hanya mengajarkan agama tauhid, namun mempelajari setting sosial ekonomi-politik masyarakat pra Islam. Paper ini adalah riset kualitatif yang bersumber dari data literatur yang dianalisis dengan metode sosio-historis interpretatif. Hasil penelitian menunjukkan bahwa kedatangan Islam di Jazirah Arab mengubah struktur ekonomi masyarakat Islam, khususnya Mekkah. Sumber ekonomi dari kegiatan bisnis berubah menjadi kegiatan militer. Perebutan sumber ekonomi dilakukan dengan cara peperangan. Perubahan cara dalam mengalahkan sumber ekonomi dilatarbelakangi oleh kekalahan bisnis Bani Hasyim dari Bani Umayyah. Nabi Muhammad Saw. semula dibenci kaum Arab (Mekkah) karena berpotensi mengganggu sumber ekonomi Arab pra Islam, lalu dielu-elukan karena berhasil mendatangkan sumber keuangan baru yang lebih mudah melalui jalan jajahan. Abstract This paper examines the efforts of the prophet Muhammad Saw. in realizing Islamic civilization by way of seizing economic and community resources from pre-Islamic Arab rulers. The efforts of the Prophet that successfully bypassed the Meccan aristocracy (Bani Umayyah) indicated that he was not only teach Muslims about monotheism, but also studying the socio-economic-political setting of pre-Islamic societies. This paper employs a qualitative research. The sources of data are taken from the study of literature, then is analized through interpretative socio-historical methods. The Data analysis has been presented descriptively. This research found that the arrival of Islam in the Arabian Peninsula has changed the economic structure of Islamic societies, especially in Mecca. The economic resources of business activities have turned into the military activities. The seizure of economic resource was carried out by war. The changes in the way of defeating economic resources, due to the defeat of Bani Hasyim’s business from Bani Umayyah. The Prophet Muhammad Saw. was initially confronted by the Arabs (in Mecca) because of his potentials to disrupt the pre-Islamic Arab economic resources, but then he was hailed for successfully bringing some new financial resources that were much easier through the colony.